Optimal Tariffs : Theory and Practice - Ibrahim, Ali (IMF Working Papers; Working Paper, 1993)
This paper examines the theory underpinning the design of optimal tariffs in a developing economy, and the experience of implementation of tariff reforms. A central issue is whether and when a case can be made for a uniform tariff structure. While theory advocates a differentiated tariff structure (except under a balance of payments objective), political economy considerations, inadequate information, and administrative convenience point to a minimally differentiated tariff structure. The experience of reform indicates that tariff structures are mainly influenced by income distribution and protection objectives. The ability to successfully reduce tariffs depends on measures taken to alleviate fiscal and balance of payments constraints.